THE INFLUENCE OF TAXATION KNOWLEDGE, MOTIVATION, PERCEPTION, AND SELF EFFICACY ON ACCOUNTING STUDENTS' INTEREST IN A CAREER AS TAX CONSULTANTS - Maulana, Muhamad Reza Arfatul; As’ari, Hasim (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
The goal of this research is to investigate how understanding of tax laws, drive, interpretation, and confidence impact the desire of accounting students at Universitas Mercu Buana Yogyakarta to pursue a profession as a tax advisor. This study utilizes a quantitative methodology through conducting a survey with 61 accounting students at Mercu Buana University Yogyakarta who have finished taxation courses. The study utilized purposive sampling to gather data via an online questionnaire. The collected information was analyzed using the multiple linear regression method facilitated by SPSS software. Findings revealed that a deep understanding of taxation greatly impacts students' desire to pursue a career as a tax advisor. The more students comprehend taxation concepts, the more likely they are to consider a profession in this field. However, the results also show that motivation, perception, and self-efficacy do not have a significant influence on interest in a career as a tax consultant. This indicates that even though students have high motivation or self-efficacy, these factors do not directly increase their interest in becoming tax consultants if their tax knowledge is inadequate.